Rotavirus vaccine coverage, completion, and compliance: A systematic literature review - Halima Tahrat; Ali Munir; Federico Marchetti (Human Vaccines & Immunotherapeutics)
Rotavirus, a leading cause of severe acute gastroenteritis in children, is largely preventable through immunization with two internationally licensed oral rotavirus vaccines (RVVs) included in national programs across over 100 countries. These RVVs are administered in either two (Rotarix™; 2D-RV) or three (RotaTeq®; 3D-RV) doses. We aimed to assess the global coverage, completion, and compliance of 2D-RV and 3D-RV in various settings, and to identify factors influencing vaccine coverage. We conducted a systematic review of PubMed and Embase for articles published between 2006 and 2021. We included 74 publications across 31 countries. RVV coverage rates and the factors associated with coverage varied widely among countries based on income level, RVV used, and the year of vaccination. Due to market bias and insufficient studies, valid RVVs coverage comparisons couldn’t be made. However, 2D-RV had better completion/compliance rates than 3D-RV in Italy, Mexico, and the US.